Understanding visitor perceptions to guide IoT-based innovations in university ecofarms: insights from Indonesia - Martuti, Nana Kariada Tri; Melati, Inaya Sari; Sumardjo, Sumardjo; Firmansyah, Adi; Dharmawan, Leonard; Darmawan, Cecep; Zaenudin, Heni Nuraeni (Frontiers in Sustainability, 2025)
This study explores visitor perceptions of UNNES Ecofarm, an integrated farming initiative by Universitas Negeri Semarang, as a foundation for guiding the development of an Internet of Things (IoT)-based automated greenhouse control system. Using a mixed-methods approach, data were collected from 209 participants, including students, educators, and professionals from various sectors. The study first assesses visitor motivations, learning experiences, and perceptions of Ecofarm’s facilities, educational quality, and sustainability practices. Findings reveal that 72% of visitors were primarily motivated by a desire to learn about integrated agriculture, with over 80% expressing positive views on accessibility and sustainability. Based on strong visitor interest in innovation and smart farming technologies, the study proceeded to develop an IoT-driven greenhouse control system to address both environmental efficiency and educational needs. This two-phase approach—first understanding user needs, then developing appropriate technology—demonstrates the importance of grounding innovation in participatory feedback. The research underscores the role of university ecofarms in sustainable development, environmental education, and technological innovation aligned with the Sustainable Development Goals.